Lecturer’s Competence and Students’ Writing Proficiency at University Level in Indonesia - Rizal Arisman; Arifuddin Hamra; Sukardi Weda (ELT Worldwide: Journal of English Language Teaching, 2017)
This research explored the influence of lecturer’s competences toward students’ writing proficiency at the English Education Study Program of Dayanu Ikhsanuddin University, Indonesia. The research question that was raised up of this research was do the lecturer competence influence students’ writing proficiency? This research aimed to investigate the influence of lecturer competence toward students’ writing proficiency. This research employed ex post facto method. The population was the fourth semester students who registered in academic year 2013/2014 for Writing III. There were 51 students were as sample of this research, selected using si.mple random sampling technique. The data collected using questionnaire and writing test. The data analyzed by applying descriptive and inferential statistics. The research found that the value of Fcount that was 3.608 at significance value was 0.035. It meant Fcount was greater than Ftable (3.608 > 2.57) and the value of significance was fewer than α (0.035 < 0.05). Those meant the regression model can predict the level of students’ writing proficiency which influenced by lecturer competence and the lecturer competence had positive and significant influence toward students’ writing proficiency at the English Education Study Program of Dayanu Ikhsanuddin University, Indonesia.